A novel recombinant serotype 4 fowl adenovirus expressing fiber-2 protein of duck adenovirus 3 - Guo, Yiwen; Lin, Yun; Xie, Quan; Zhang, Wenyuan; Xu, Zhenqi; Chao, Yifei; Cao, Xudong; Jiang, Huiru; Li, Han; Li, Tuofan; Wan, Zhimin; Shao, Hongxia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Recently, the highly pathogenic serotype 4 fowl adenovirus (FAdV-4) and duck adenovirus 3 (DAdV-3) were outbroken and widespread, causing substantial economic losses to the duck industry. Therefore, there is an urgent need to generate a recombinant genetic engineering vaccine candidate against both FAdV-4 and DAdV-3. In this study, a novel recombinant FAdV-4 expressing the Fiber-2 protein of DAdV-3, designated as rFAdV-4-Fiber-2/DAdV-3, was generated based on CRISPR/Cas9 and Cre-LoxP systems. Indirect immunofluorescence assay (IFA) and western blot (WB) showed that the Fiber-2 protein of DAdV-3 in rFAdV-4-Fiber-2/DAdV-3 was expressed successfully. Moreover, the growth curve revealed that rFAdV-4-Fiber-2/DAdV-3 replicated efficiently in LMH cells and even showed a stronger replication ability compared to the wild type FAdV-4. The generation of the recombinant rFAdV-4-Fiber-2/DAdV-3 provides a potential vaccine candidate against both FAdV-4 and DAdV-3.